Peran Rehabilitasi Therapeutic Community Dalam Pemulihan Narapidana Narkotika di Lapas Narkotika Kelas IIA Jakarta - Martcelino, Aldo; Yuska, Syahrial (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the role of therapeutic community (TC) rehabilitation in the recovery process of drug offender inmates at the Narcotics Penitentiary Class IIA Jakarta. Rehabilitation using the TC approach is expected to change the mindset and behavior of inmates by providing useful life skills and reducing the risk of relapse. This research uses a qualitative approach with in-depth interviews conducted with inmates, prison officers, and other relevant parties. The results show that the TC rehabilitation program has made a significant contribution to the recovery of inmates, in terms of mental, social, and life skills aspects. This program provides a supportive environment for behavioral change, with an emphasis on social interactions among inmates who support one another. However, challenges still exist, such as limited facilities and inadequate family involvement. This study recommends strengthening collaboration between prison authorities, families, and society to support the sustainability of the drug offenders' recovery. Keywords: rehabilitation, therapeutic community, drug offender inmates